Music streaming services and the drivers of customer purchase - Barata, Mariana Lopes (2023)
Purpose- The music industry has undergone tremendous changes in relation to its production, distribution, and consumption habits due to the exponential development of new technologies, namely streaming platforms. This study aims to understand the factors that influence music consumption through streaming platforms, particularly analysing the differences between premium and freemium users on the intention to adopt premium (paid) versions of a music streaming service. Methodology- UTAUT2 model (version of the Unified Theory of Acceptance and Use of Technology, applied to the consumer side) was used as framework. Based on data collected from 324 music streaming services users (premium and freemium), this study was tested using structural equation modelling (SEM). Findings- Our findings, focused fundamentally on the initial period of pandemics (2020-2021), confirm that facilitating conditions, price value and performance expectancy play the most important role in influencing the intention to use a paid music streaming service for the premium sample. However, the freemium sample finds habit, price value and hedonic motivation the variables most relevant. Conclusion- The research contributes insights into music streaming services consumer behaviour, providing several theoretical and practical implications to music streaming services providers.